Peran Biaya Produksi dalam Menentukan Keputusan Produsen - Muhammad Raghid Alfatiy; Raihan Ade Ghuffar; Reni Ria Armayani Hasibuan (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
The purpose of this research is to examine how production costs factor into producer choices, particularly those pertaining to output volume, selling price estimation, and company growth strategies. The research examined micro and small business players in Kediri Regency, East Java, employing a descriptive quantitative technique. The findings demonstrate that the production cost structure, particularly the preponderance of variable costs, considerably affects the quantity of output and the margin for price adjustment. It has additionally been demonstrated that saving money encourages manufacturers to take risks and grow their companies. Moreover, management accounting-based cost tracking, waste reduction, and sourcing local raw materials are all cost management tactics that impact a company's strength and ability to compete. Producers' long-term strategic decision-making is therefore influenced by effective production cost management, which in turn affects operational sustainability.